1985
DOI: 10.1002/star.19850370806
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Epichlorhydrin with Carbohydrate Polymers. Part I. Starch Reaction Kinetics

Abstract: The starch‐epichlorohydrin (ECH) reaction follows second order kinetics, first order with respect to ECH as well as starch. The activation energy for the reaction is of the order of 38 kJ/mole and the temperature coefficient K323/K303 is of the order of 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Strengthening the bonding between starch chains through cross-links might have increased the resistance of the granules to swelling, leading to the higher pasting temperature and lower peak viscosity. Introducing low degrees of cross-linking in starch has been reported to increase the peak and cold paste viscosities of starch (Kartha and Srivastava, 1985). In this study, cross-linked rice and maize starch showed an increase in the peak and final viscosities.…”
Section: Pasting Propertiesmentioning
confidence: 54%
“…Strengthening the bonding between starch chains through cross-links might have increased the resistance of the granules to swelling, leading to the higher pasting temperature and lower peak viscosity. Introducing low degrees of cross-linking in starch has been reported to increase the peak and cold paste viscosities of starch (Kartha and Srivastava, 1985). In this study, cross-linked rice and maize starch showed an increase in the peak and final viscosities.…”
Section: Pasting Propertiesmentioning
confidence: 54%
“…Since starch microgels may swell, a fit of our data presented in Fig. 6d according to [12] Table 4) are much larger than expected for uncharged starch microgels (compare to, for example, [8]), which is probably due to surface charges.…”
Section: Viscosity Measurementsmentioning
confidence: 77%
“…In section 3.1, starch microgels were shown to be spherical, and assuming Eq. [8] is valid, the extrapolation of a linear fit of the reduced viscosity data to the zero particle concentration (c p → 0) should give the mass intrinsic viscosity ([η]). From [η], the particle hydrodynamic volume is then deduced by employing Eq.…”
Section: Viscosity Measurementsmentioning
confidence: 99%
See 2 more Smart Citations